Projected flow regimes and biodiversity changes under climate change in the planning western route source areas of the South-to-North Water Diversion Project - Di Fan; Sidong Zeng; Hong Du; Yuanxin Ren; Jun Xia (Ecological Indicators, 2023)
Scientific evaluation of the eco-hydrological regimes is of great significance for water resource management and aquatic ecosystem protection. The paper took the western route source areas (WRSA) of the South-to-North Water Diversion Project (SNWDP) as the research region. In order to quantify climate-induced eco-hydrological effects, a general framework was proposed to predict changes in flow regimes and fluvial biodiversity under climate change: The coupling of Global Climate Models (GCMs) and the Distributed Time Variant Gain Model (DTVGM) was used to simulate discharge under different climate conditions. Based on Indicators of Hydrologic Alteration (IHA), changes in eco-hydrological regimes were evaluated by using the Range of Variability Approach (RVA), assessment of overall hydrological change degree (D0), and Shannon index (SI). Changes in discharge, flow regimes, and fluvial biodiversity of WRSA were analyzed during the projected period (2041–2100) compared to the base period (1960–2014). According to the projections, under four SSPs-RCPs scenarios, the future discharge of WRSA increases significantly compared to the base period. D0 of WRSA is moderately or severely changed, and hydrological changes are mainly reflected in high flows such as monthly median flows during flood season, maximum flows, and high pulse duration. While flow regimes are disturbed, SI values of WRSA keep rising and the biodiversity is improved. The increase of discharge and SI becomes progressively greater with elevated radiation intensity, and the quantity of severely altered indicators of IHA increases. In conclusion, future hydrological alterations in SNWDP are expected to further intensify with higher levels of climate change, and these changes are generally conducive to the improvement of fish biodiversity.